Step
*
3
1
1
1
1
of Lemma
cos-sin-equation-nc
1. f : ℝ ⟶ ℝ
2. g : ℝ ⟶ ℝ
3. ∀x,y:ℝ.  ((x = y) 
⇒ (f(x) = f(y)))
4. ∀x,y:ℝ.  ((x = y) 
⇒ (g(x) = g(y)))
5. ∀x,y:ℝ.  (f(x - y) = ((f(x) * f(y)) + (g(x) * g(y))))
6. ∃a:ℝ. f(a) ≠ f(r0)
7. ∀x,y:ℝ.  (f(x - y) = f(y - x))
8. ∀y:ℝ. (f(-(y)) = f(y))
9. ∃b:ℝ. g(-(b)) ≠ g(b)
10. ∀x,y:ℝ.  (f(x - y) = ((f(x) * f(y)) + (g(-(x)) * g(-(y)))))
11. ∀x,y:ℝ.  ((g(-(x)) * g(-(y))) = (g(x) * g(y)))
12. ∀x:ℝ. (g(-(x))^2 = g(x)^2)
⊢ ∀y:ℝ. (g(-(y)) = -(g(y)))
BY
{ ((Assert ∃d:ℝ. g(d) ≠ r0 BY
          (ExRepD THEN (InstLemma `rneq-cases` [⌜g(-(b))⌝;⌜g(b)⌝;⌜r0⌝]⋅ THEN Auto) THEN D -1 THEN Auto))
   THEN D -1
   ) }
1
1. f : ℝ ⟶ ℝ
2. g : ℝ ⟶ ℝ
3. ∀x,y:ℝ.  ((x = y) 
⇒ (f(x) = f(y)))
4. ∀x,y:ℝ.  ((x = y) 
⇒ (g(x) = g(y)))
5. ∀x,y:ℝ.  (f(x - y) = ((f(x) * f(y)) + (g(x) * g(y))))
6. ∃a:ℝ. f(a) ≠ f(r0)
7. ∀x,y:ℝ.  (f(x - y) = f(y - x))
8. ∀y:ℝ. (f(-(y)) = f(y))
9. ∃b:ℝ. g(-(b)) ≠ g(b)
10. ∀x,y:ℝ.  (f(x - y) = ((f(x) * f(y)) + (g(-(x)) * g(-(y)))))
11. ∀x,y:ℝ.  ((g(-(x)) * g(-(y))) = (g(x) * g(y)))
12. ∀x:ℝ. (g(-(x))^2 = g(x)^2)
13. d : ℝ
14. g(d) ≠ r0
⊢ ∀y:ℝ. (g(-(y)) = -(g(y)))
Latex:
Latex:
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  g  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y)))
4.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (g(x)  =  g(y)))
5.  \mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  ((f(x)  *  f(y))  +  (g(x)  *  g(y))))
6.  \mexists{}a:\mBbbR{}.  f(a)  \mneq{}  f(r0)
7.  \mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  f(y  -  x))
8.  \mforall{}y:\mBbbR{}.  (f(-(y))  =  f(y))
9.  \mexists{}b:\mBbbR{}.  g(-(b))  \mneq{}  g(b)
10.  \mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  ((f(x)  *  f(y))  +  (g(-(x))  *  g(-(y)))))
11.  \mforall{}x,y:\mBbbR{}.    ((g(-(x))  *  g(-(y)))  =  (g(x)  *  g(y)))
12.  \mforall{}x:\mBbbR{}.  (g(-(x))\^{}2  =  g(x)\^{}2)
\mvdash{}  \mforall{}y:\mBbbR{}.  (g(-(y))  =  -(g(y)))
By
Latex:
((Assert  \mexists{}d:\mBbbR{}.  g(d)  \mneq{}  r0  BY
                (ExRepD
                  THEN  (InstLemma  `rneq-cases`  [\mkleeneopen{}g(-(b))\mkleeneclose{};\mkleeneopen{}g(b)\mkleeneclose{};\mkleeneopen{}r0\mkleeneclose{}]\mcdot{}  THEN  Auto)
                  THEN  D  -1
                  THEN  Auto))
  THEN  D  -1
  )
Home
Index